FAHAM MAHABBAH DAN MA’RIFAH DALAM TASAUF ISLAM - Hasnawati, Hasnawati (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This study aimed to examine the fenomenon of Mahabbah and Ma’rifah and the development of it in lates and today, and the relationship with the educatioanal of islamic future way of thinking. The purpose of this study is to show the teaching of the fenomenon Mahabbah and Ma’rifah. This study using descriptive kualitative methode, historical approach with library research technic. This descriptive type of research used document. Having analyzed the existing sample, writer found firstly Mahabbah and Ma’rifah was influenced by Rabi’ah al-Adawiyah and Zunnun al-Misri. The concept of Mahabbah and Ma’rifah are the key to close and love God in the same time. Secondly Mahabbah and Ma’rifah are the highest level of “hub” to God, someone need to see it as a global, and not part by part. The result of this study found the idiology and the teaching of Rabi’ah al-Adawiyah and Zunnun al-Misri was suitable and in the line with principle of Islam.